Syncope: epidemiology, etiology, and prognosis - da Silva, Rose M. F. L. (Frontiers in Physiology, 2014)
Syncope is a common medical problem, with a frequency between 15% and 39%. In the general population, the annual number episodes are 18.1 to 39.7 per 1000 patients, with similar incidence between genders. The first report of the incidence of syncope is 6.2 per 1000 person-years. However, there is a significant increase in the incidence of syncope after 70 years of age with rate annual 19.5 per thousand individuals after 80 years. It presents a recurrence rate of 35% and 29% of physical injury. Among the causes of syncope, the mediated neural reflex, known as neurocardiogenic or vasovagal syncope, is the most frequent. The others are of cardiac origin, orthostatic hypotension, carotid sinus hypersensitivity, neurological and endocrinological causes and psychiatric disorders. The diagnosis of syncope can be made by clinical method associated with the electrocardiogram in up 50% of patients. Its prognosis is determined by the underlying etiology specifically the presence and severity of cardiac disease. The annual mortality can reach between 18 and 33% if cardiac cause, and between 0 and 12% if the noncardiac cause. Thus, it is imperative to identify its cause and risk stratification for positive impact in reducing morbidity and mortality.